Analysis financial ratio on financial performance of banks with problem finance as intervening variables - Safitri, Safitri; Nabila, Rifda (UIN Salatiga, 2023)
The purpose of this study was to analyze the effect of CAR, BOPO and FDR on ROA with Non-performing Financing as an Intervening Variable in Islamic Commercial Banks for the 2016-2020 period. Where this research uses quantitative research using regression analysis as data analysis. This study uses secondary data in the form of panels using the annual data of each Islamic commercial bank selected as the research sample in the 2016-2020 period. The data obtained were then analyzed using the Eviews 10 application tool. The results of this study indicate that the CAR, BOPO, FDR and NPF variables have a partial effect on ROA. The CAR, FDR and NPF variables have no significant negative effect on ROA, while the BOPO variable has a significant negative effect on ROA. And the NPF variable cannot mediate the effect of CAR, BOPO and FDR on ROA. And the results of the research on the ROA of Islamic Commercial Banks before the pandemic (2019) and during the pandemic (2020) using the Wilcoxon Signed Rank Test showed that there were significant differences.